Stroke volume estimation by rheo-echocardiography during atrial fibrillation converted to sinus rhythm - PAŁKO, Tadeusz; KOMPIEL, Leonard; ILMURZYŃSKA, Krystyna (Archives of Acoustics, 1984)
The impedance rheographic and echocardiographic methods were used to investigate changes in the stroke volume (SV) and the cardiac output (CO) in the course of atrial fibrillation and after electroversion. 12 patients were examined. CO increased on average by 11 per cent and 9 per cent after electro-version using respectively rheographic and echocardiographic methods.